Pilot-scale phosphate recovery from wastewater to create a fertiliser product: An integrated assessment of adsorbent performance and quality. (1st January 2023) - Pap, Sabolc; Zhang, Huiyi; Bogdan, Aleksandra; Elsby, Derek T.; Gibb, Stuart W.; Bremner, Barbara; Taggart, Mark A.
Highlights: Pilot-scale phosphate removal was explored from final WWTP effluents. Microprecipitation and ligand-exchange were postulated as P adsorption mechanisms. ∼2.5% of P2 O5 content, no inorganic pollutants and pathogens were detected in CCM. Low water solubility indicated slow phosphate release kinetics in soil. FILTRAFLO™-P with CCM could serve as a water polishing and phosphate harvesting unit. Abstract: Eutrophication and the predicted limited future availability of rock phosphate has triggered the increased development of phosphorus (P) recovery technologies, however, for remote regions, recovery solutions are still limited. Here, we report on a novel pilot-scale technology (FILTRAFLO TM -P reactor) to recover phosphate (PO4 3− ) from wastewater effluent through a filtration/adsorption process in a rural setting. This unit employs enhanced gravitational filtration through adsorption media (here, a novel KOH deacetylated crab carapace based chitosan-calcite material (CCM)) with continuous self-backwashing. Trials were designed to assess how the FILTRAFLO TM -P unit would operate under 'real' conditions (both at low and high PO4 3− levels), and to ascertain the effectiveness of the adsorbent to recover phosphate from final effluent. High removal was achieved at low phosphate concentrations, bringing the residual effluent PO4 3− level below 1 mg/L (EU limit for sensitive water bodies), while phosphate was efficiently harvested (at more than 50%) at higher PO4 3− levels. Surface microprecipitation and inner-sphere complexation were postulated as the main PO4 3− adsorption mechanisms through XRD, XPS and EDX elemental mapping. Further, a quality assessment of the P-enriched CCM (which could be used as a potential soil amendment) was undertaken to consider elemental composition, microbiological assessment and quantification of organic micropollutants. Quality analysis indicated ∼2.5% P2 O5 present, trace levels (well below legislative limits) of heavy metals and extremely low levels of organic pollutants (e.g., PCBs, pharmaceuticals). No detectable levels of target bacterial pathogens were observed. Pot trials showed that ryegrass cultivated with the addition of the CCM adsorbent achieved higher plant dry matter and P concentration when compared to unfertilised controls, with a slow-release kinetic pattern. This study showed that CCM used with the FILTRAFLO TM -P pilot reactor has high potential to recover phosphate from effluents and encourage resource recovery via bio-based management of waste. Graphical abstract: Image, graphical abstract